(3GdeSFhdjI GdbGfhfjI ddWHjH hGdeSJTai hGdUjOdj eY TQM bGfhf JfXje RQY GdCYVGA Qbe (B5 (3dSfI (B2010 /s - (3GdChOf, SejQ YHO GdSejYs ((3GdEScfOQjI, eUQ (B:s (3efTCI GdeYGQa,s, 2011)
(3jJfGhd cJGH (B((3GdeSFhdjI GdbGfhfjI ddWHjH hGdeSJTai hGdUjOdj eY TQM bGfhf JfXje RQY GdCYVGA Qbe (B5 (3dSfI (B2010) (3hGdPj bGe HJCdjag (B((3GdCSJGP SejQ YHO GdSejY GdChOf(B) (3aj MhGdj (B(501) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdeSFhdjI GdLfGFjI ddCWHGA(B) (3GdeMJhjGJ GdJGdjI (B: (3GdHGH GdChd (B: (3eSFhdjI GdWHjH, GdaUd GdChd (B: (3TQhW eTQhYjI GdYed GdWHj, GdaUd GdKGfj (B: (3CQcGf GdeSFhdjI GdWHjI, GdaUd GdKGdK (B: (3OYhi GdeSFhdjI GdWHjI(B... (3EdN(B.s
(3cJGHI GdcheHjhJQ (B: (3GdeDda(B.s
Keywords: (3GdeSFhdjI GdLfGFjI ddCWHGAs -- (3eUQs; (3GdeSFhdjI GdLfGFjI ddUjGOdIs -- (3eUQs; (3GdWHs -- (3bhGfjf hJTQjYGJs; (3RQY GdCYVGAs -- (3bhGfjf hJTQjYGJs